The Combination of Progressive Muscle Relaxation and Aromatherapy on Blood Sugar Levels in Type 2 Diabetes - Mardiyah, Raiza Naimatul; Cahyati, Yanti; Aryanti, Dewi; Kuswandi, Asep (PT. Pubsains Nur Cendekia, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic disease with increasing prevalence in Indonesia, largely due to lifestyle changes. Blood glucose control in T2DM patients not only relies on pharmacological therapy but can also be supported by non-pharmacological interventions such as progressive muscle relaxation and lavender aromatherapy. These therapies are believed to lower blood glucose levels by reducing stress and promoting relaxation. Aims: To examine the effect of a combination of progressive muscle relaxation and lavender aromatherapy on blood glucose levels in T2DM patients. Method: A quasi-experimental design with a pretest-posttest control group approach was used. A total of 30 hospitalized T2DM patients at a hospital in Tasikmalaya were recruited through incidental sampling and divided equally into intervention and control groups. The intervention group received progressive muscle relaxation for 30 minutes and lavender aromatherapy for 5 minutes twice daily over three consecutive days. The control group received standard hospital care. Random blood glucose levels were measured before and after the intervention. Results: A significant reduction in the intervention group from 265.93 mg/dL with an SD of 41.24 to 220.40 mg/dL with an SD of 51.67 (p = 0.000), while the control group showed a non-significant decrease from 281.13 mg/dL with an SD of 45.55 to 268.87 mg/dL with an SD of 51.01 (p = 0.205). A significant difference was also observed between the two groups after the intervention (p = 0.015). Conclusion: the combination of progressive muscle relaxation and lavender aromatherapy was effective in lowering blood glucose levels in T2DM patients. It can be considered as a complementary non-pharmacological therapy in diabetes management.